Recent developments in recognition elements for chemical sensors and biosensors - Justino, Celine I. L.
Recognition elements, also known as target receptors, are important parts of chemical sensors and biosensors since they are responsible for the recognition of target analytes of interest. Although recent recognition elements were synthesized in the laboratory or selected in vitro, their combination with nanomaterials also aroused the interest of researchers due to improvements in the analytical performance of chemical sensors and biosensors as a consequence of the enhanced properties of such nanostructures. This review discusses recent developments in recognition elements, both classical, such as enzymes and antibodies, and recent, such as aptamers and phages, integrated into chemical sensors and biosensors in the food, clinical and environmental fields.